Pengujian Kepatuhan Asersi LADK Pada Audit Dana Kampanye Partai Politik dan Calon Legislatif: Studi Kasus Pada KAP LMR - Innaha Fadhila Nurmawaddah; Diah Hari Suryaningrum (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2024)
This research aims to analyze compliance with assertions in the Initial Campaign Funds Report (LADK) from several cities or regencies or in one province in Indonesia, focusing on specific cities and regencies. The research method used is descriptive-qualitative with a case study approach, and the technical data analysis used is descriptive analysis, which is used to describe the assertion testing procedures for the Initial Campaign Funds Report (LADK) procedures implemented by KAP LMR. The research findings reveal significant variations in compliance with LADK across different regions, with some areas facing challenges in verifying the assertions in their reports. The implications underscore the need for enhanced understanding, oversight, and enforcement of regulations to ensure integrity and transparency in campaign fund management by political parties and legislative candidates.